Rapid room temperature crystallization of TiO2 nanotubes. Issue 12 (6th March 2017) - K., Aijo John; Thankamoniamma, Manju; Puigdollers, Joaquim; R., Anuroop; Pradeep, B.; Shripathi, Thoudinja; Philip, Rachel Reena
Abstract : This paper reports a very efficient and reproducible technique for room temperature crystallization of titanium dioxide in a record time of 5 minutes, by application of alternating voltage square pulses. Abstract : This paper reports a very efficient and reproducible technique for room temperature crystallization of titanium dioxide in a record time of 5 minutes, by application of alternating voltage square pulses. The well aligned tubular formation of crystalline nanotubes is confirmed through various characterization techniques, and the mechanism of crystallization is explained based on the pulse induced electrophilic–nucleophilic reaction. This ultrafast pulsed crystallization method provides a viable alternative for the widely used post fabrication thermal annealing and is highly applicable in device fabrication.